An integrated pore size distribution measurement method of small angle neutron scattering and mercury intrusion capillary pressure - Rui Shen (Nature Portfolio, 2021)
Abstract Small-angle neutron scattering and high-pressure mercury intrusion capillary pressure testing are integrated to analyze the pore size distribution of the broad sense shale oil reservoir samples of the Permian Lucaogou Formation in the Jimsar Sag, Junggar Basin, China. The results show that, compared with the measurement method integrating gas adsorption and mercury intrusion, combination of small-angle neutron scattering and mercury intrusion can more accurately characterize full-scale pore size distribution. The full-scale pore size distribution curve of the rock samples in the study area includes two types: the declining type and submicron pore-dominated type. The declining type is mainly found with silty mudstone and dolomitic mudstone, and most of its pores are smaller than 80 nm. Silt-fine sandstones and dolarenite are mostly of the submicron pores-dominated type, with most pores smaller than 500 nm. They also present large specific pore volumes and average pore diameters of macropores and are the favorable lithogenous facies for development of high-quality reservoirs.